Causality and Connectives : From Grice to Relevance. - Bardzokas, Valandis (Pragmatics & beyond, 2012)
The book explores finely-grained distinctions in causal meaning, mostly from a relevance-theoretic perspective. To increase the challenge of this double task, i.e. a thorough as well as satisfactory account of cause and a detailed assessment of the theoretical model employed to this end, the current study involves an investigation carried out by way of contrasting the prototypical causal exponents of Modern Greek subordination, i.e. epeidi and?iati. In addition, this objective is achieved in the methodological framework of contrasting a range of contextual applications of the two connectives.